Longitudinal study of small ruminant zoonoses in Tana River, Kenya - Wainaina, Martin; Lindahl, Johanna F.; Dohoo, I.; Mayer-Scholl, A.; Roesel, Kristina; Mbotha, Deborah; Roesler, U.; Grace, Delia; Bett, Bernard K.; Al Dahouk, S. (International Livestock Research Institute, 2022)
Objectives Bacterial infections are the leading causes of non-malarial fevers in Africa. Brucellosis, leptospirosis, and Q fever are priority zoonoses in Kenya, but little information on their epidemiology is available to date. Therefore, we implemented this longitudinal study by following up 316 small ruminants on September, November, and December 2014, and January, March, and June 2015. Materials and methods Sampling was done in pastoral, irrigated, and riverine settings in Tana River County. We aimed at estimating the disease burden, disease frequency, and associated risk factors for both exposure and seroconversion. We tested for: (i) Coxiella burnetii using an IgG ELISA, (ii) Leptospira spp. using the microscopic agglutination test, and (iii) Brucella spp. using the complement fixation test. We further tested seropositive animals by real-time PCR. Results The overall seroprevalence estimates were highest for Coxiella burnetii (20.89%, 95% confidence interval [CI]: 16.54-25.79), followed by those of Leptospira spp. (15.97%, 95% CI: 12.09-20.51) and Brucella spp. (1.27%, 95% CI: 0.35-3.21). Despite this, we observed more seroconversions for Leptospira spp. (27) than Coxiella burnetii (10) and Brucella spp. (0). Analysis of the risk factors and incidence rate estimations are still ongoing. Three animals were positive by PCR for Brucella spp. either consistently or intermittently for almost the entire study period, demonstrating the possibility of prolonged periods of transmission. One animal was also PCR-positive for C. burnetii, but we detected no pathogenic leptospires. The most prevalent leptospiral serovar was Ballum, but evidence of paradoxical reactions was seen. Therefore, infective serovars in the area should be proven by isolation of leptospires. Conclusions The high number of seroconverting animals in the study area shows the need for surveillance and control measures to reduce animal disease burden and possible human exposure.